Etude physico-chimique de l’eau de mer au niveau de la zone industrielle de Bethioua - BEY, Samira (My University, 2019)
This work concerns, on the one hand, the study of the physico-chemical parameters of seawater in the Bethioua industrial zone and, on the other hand, a diagnosis of the state of its pollution in industrial discharges. To carry out this study, monthly seawater samples between June and July 2019 were taken at three different stations in the area. The choice of area is mainly linked to industrial activities near this coastal area. The results obtained show significant variations in the various physico-chemical parameters of seawater such as: pH, salinity, conductivity, temperature, suspended solids, NO2- and NH3, etc. At the end of the results obtained, an interpretation of the data was made, on the basis of the degree of contamination of the marine environment in this area, concluding that the physico-chemical quality of the seawater in the area of Bethioua is polluted and of poor quality.
Keywords: Sea water; physico-chemical parameters; industrial zone; Bethioua; pollution